Pathogenesis of Autoimmune Cytopenias in Inborn Errors of Immunity Revealing Novel Therapeutic Targets - Cortesi, Manuela; Soresina, Annarosa; Dotta, Laura; Gorio, Chiara; Cattalini, Marco; Lougaris, Vassilios; Porta, Fulvio; Badolato, Raffaele (Frontiers in Immunology, 2022)
Autoimmune diseases are usually associated with environmental triggers and genetic predisposition. However, a few monogenic autoimmune diseases have been identified, especially in children. These diseases may be the expression, isolated or associated with other symptoms, of an underlying inborn error of immunity (IEI). Autoimmune cytopenias, including immune thrombocytopenic purpura (ITP), autoimmune hemolytic anemia (AIHA), autoimmune neutropenia (AN), and Evans’ syndrome (ES) are common presentations of immunological diseases in the pediatric age, with at least 65% of cases of ES genetically determined. Autoimmune cytopenias in IEI have often a more severe, chronic, and relapsing course. Treatment refractoriness is another hallmark of autoimmune cytopenia within an underlying IEI. The mechanisms underlying autoimmune cytopenias in IEI include cellular or humoral autoimmunity, immune dysregulation in form of hemophagocytosis or lymphoproliferation with or without splenic sequestration, bone marrow failure, myelodysplasia, or secondary myelosuppression. Genetic characterization of autoimmune cytopenias is of fundamental importance as an early diagnosis improves the outcome and allows the setting up of a targeted therapy, such as CTLA-4 IgG fusion protein (Abatacept), small molecule inhibitors (JAK-inhibitors), or gene therapy. The last it is currently one of the most appealing targeted therapeutic approaches to treat selected inborn errors of immunity. Even in the absence of specific targeted therapies, however, whole exome genetic testing (WES) for children with chronic multilineage cytopenias should be considered as an early diagnostic tool for disease diagnosis and genetic counseling.